Effect of Al ions on adsorption efficiency of mesoporous organosilica for water treatment - Ani, Mohd Hanafi; Mohd Hatta, Maziati Akmal; Othman, Raihan (Trans Tech Publications, Switzerland, 2012)
Porous organosilica is a promising material to be applied in water treatment due to high adsorption capacity of contaminants. Sol-gel method was used to fabricate mesoporous organosilioca from triblock copolymers, poly(ethylene oxide)-b-poly(propylene oxide)-b-poly(ethylene oxide) as the template and tetraethylorthosilicate as silicate source. The organosilica is doped with Al powder and Al2SO3 in order to evaluate the effect of ions on their adsorption capacity. It was demonstrated that the adsorption capacity is proportional to Al concentration, and inversely proportional to porosity. Metallic compound doped in organosilica enhances the remediation process and optimize the water treatment process. Moreover, impregnation the samples into cellulosic sponge improves the adsorption efficiency by 25%.